Assigning firm-level GHGE reductions based on national goals - Mathematical model & empirical evidence. (1st January 2018) - Jackson, Jacob; Belkhir, Lotfi
Abstract: The so-called Paris Agreement, signed by 195 countries, has led to the setting of some ambitious target reductions in greenhouse gas emissions by most developed countries. The over-arching goal of those reduction targets is to limit global warming to less than 2 o C compared to pre-industrial levels. Yet, despite these commitments from the highest governance levels, there is still no deterministic model on how these national target reductions will be cascaded down to the commercial sector, which accounts for the lion's share of these emissions. In this paper, we present a novel framework which enables the setting, measurement and tracking of the emissions performance of every commercial entity based on a single metric. We further present empirical evidence from the automotive industry to illustrate how the model helps to readily identify the low versus high performers. The model also reveals one car company that stands out as the industry benchmark by already exceeding the performance required by the 2025 emissions target set by the US. The model proves successful in achieving the objectives of being: science-based, goal-driven, equitable, comparable and actionable, and as such can be readily used to accurately compare competitors from the same industry and provide the basis of a more equitable, performance-based carbon tax market, as well as the ability to assess accurately how well a specific country is meeting its reduction quota and how the various industry sectors are impacting that goal. Graphical abstract: We present a novel framework which enables the setting, measurement and tracking of the emissions performance of every commercial entity based on a single metric. We further present empirical evidence from the automotive industry to illustrate how the model helps to readily identify the low versus high performers. The model reveals one car company, i.e. BMW, that stands out as the industry benchmark by already exceeding the performance required by the 2025 US emissions target. The model proves successful in achieving the objectives of being: sciencebased, goal-driven, equitable, comparable and actionable, and as such can be readily used to accurately compare competitors from the same industry and provide the basis of a more equitable, performance-based carbon tax market. Image 1 Highlights: A novel framework which enables the setting, measurement and tracking of emissions performance. A single metric allowing for immediate differentiation between low and high performers. A mathematical model for the setting of a firm's emission intensity and allowable emissions to ensure compliance with national targets. Empirical evidence from the automotive industry.